PENERAPAN METODE RAD DALAM IMPLEMENTASI E-COMMERCE BERBASIS WEB PADA CV. TENDA TEDUH ABADI - Tian Ahmad Setiawan; Wiyanto Wiyanto; Agus Suwarno (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
In this research, the problem of making e-commerce is formulated in dealing with time delays in the sales process and goods data collection at CV. TENDA TEDUH ABADI which is still done conventionally by applying the RAD (Raphid Application Development) method to implementing web-based e-commerce. The e-commerce development process uses the native PHP programming language, Bootstrap CSS, and user interface design uses the Figma application. The goal in making this e-commerce is to help the sales process and inventory of goods be more integrated and up to date, the results obtained are in the form of e-commerce web-based online sales that can be used in CV. TENDA TEDUH ABADI to help the process of selling and collecting goods by the factory admin to be more integrated and up to date.